2007
DOI: 10.1097/ana.0b013e318051743d
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of the Neuroprotective Effects of Thiopental Sodium, Propofol, and Halothane on Brain Ischemia in the Gerbil: Effects of the Anesthetics on Ischemic Depolarization and Extracellular Glutamate Concentration

Abstract: Although propofol and thiopental are commonly used as neuroprotective agents, it has not been determined which is more neuroprotective. This study was designed to quantitatively evaluate the neuroprotective effects of thiopental, propofol, and halothane on brain ischemia by determining P50, ischemic time necessary for causing 50% neuronal damage. Gerbils were anesthetized with thiopental, propofol, or halothane and underwent 2-vessel occlusion (0, 3, 5 or 10 min). Direct current potentials were measured in bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Numerous anesthetics have been tested to delay the time to depolarization, because their inhibitory effect on CMR is expected to slow ATP depletion in ischemic tissue. Using either in vivo or in vitro preparations, lidocaine [52], thiopental [53], pentobarbital [54], propofol [55], isoflurane [56], desflurane [57], and sevoflurane [58] have all been reported to delay depolarization onset.…”
Section: Ischemic Depolarizationsmentioning
confidence: 99%
“…Numerous anesthetics have been tested to delay the time to depolarization, because their inhibitory effect on CMR is expected to slow ATP depletion in ischemic tissue. Using either in vivo or in vitro preparations, lidocaine [52], thiopental [53], pentobarbital [54], propofol [55], isoflurane [56], desflurane [57], and sevoflurane [58] have all been reported to delay depolarization onset.…”
Section: Ischemic Depolarizationsmentioning
confidence: 99%
“…Recent studies showed that propofol improves neurological outcome and decreases infarct size in animal models of cerebral ischemia [5,6]. Several hypotheses about this neuroprotective properties of propofol are: scavenging free radicals derived from the lipid peroxidative reaction [7][8][9]; up-regulation of GABA A -mediated inhibition of synaptic transmission and suppression of glutamate release in cerebral ventricles [10][11][12]; and inhibition of N-methyl-Daspartate (NMDA) receptor and Ca 2? overload [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The neuroprotective effect of propofol is the result of a number of mechanisms, including reducing the brain oxygen metabolism rate, removing the oxygen free radicals (12,13), activating the c-aminobutyric acid type A receptor (14), inhibiting the glutamate receptors (15), reducing the extracellular glutamate concentration (16) and increasing the glutamic acid salt intake (17) via inhibiting the release of glutamate-dependent Na + channels. In the present study, propofol was shown to significantly downregulate the expression levels of CCL2 and CCR2 in the hippocampal tissues, indicating that propofol may decrease the inflammatory reactions caused by ischemia during reperfusion.…”
Section: Discussionmentioning
confidence: 99%